A Hacking Epidemic That Hits Few Consumers in the Wallet. - POPPER, NATHANIEL (New York Times, 2015)
Several graphs showing decline in the cost to consumers in case of data breaches in the U.S. which include data on total number of data breaches in the U.S., and total cost of identity fraud in the U.S.